Improving students' mathematics self-efficacy: A systematic review of intervention studies - Zakariya, Yusuf F. (Frontiers in Psychology, 2022)
Self-efficacy is an integral part of personal factors that contributes substantially to students’ success in mathematics. This review draws on previous intervention studies to identify, describe, and expose underlying mechanisms of interventions that foster self-efficacy. The findings show that effective self-efficacy interventions can be categorised into three categories using their underlying mechanisms: those that directly manipulate sources of self-efficacy to foster the construct, and those that either embed self-efficacy features in teaching methods or in learning strategies. Specific examples of interventions that fall in each of these three categories are described including their features and the underlying mechanisms that improve students’ mathematics self-efficacy. I argue for the two “most effective” interventions that foster self-efficacy and their relevance to either pre-university or university students with implications for teaching and learning mathematics.